2011
DOI: 10.1108/14717791111163604
|View full text |Cite
|
Sign up to set email alerts
|

Audit of fidelity of clinicians to the Mental Capacity Act in the process of capacity assessment and arriving at best interests decisions

Abstract: PurposeThe purpose of this paper is to evaluate health professionals' fidelity to the Mental Capacity Act (MCA) principles on determining mental capacity and arriving at best interests decisions in the care of individuals found to lack the relevant decision‐making capacity.Design/methodology/approachA retrospective review of the case records of 68 patients previously determined by clinicians as lacking mental capacity in at least one of three identified areas: treatment consenting capacity, capacity to decide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
3
14
0
Order By: Relevance
“…, , Bond & Lowton , Sorinmade et al . ), care home staff (Manthorpe et al . ), community healthcare staff (Alonzi et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…, , Bond & Lowton , Sorinmade et al . ), care home staff (Manthorpe et al . ), community healthcare staff (Alonzi et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, Sorinmade et al . conducting a hospital case records review reported ‘patchy documentation of the legal criteria used in capacity assessment’, and furthermore ‘clinicians only partially followed the procedure prescribed by the MCA in determining best interest’ (p. 174).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research within the past three years has suggested that improvements were needed with regard to the implementation of the MCA particularly within health (Phair and Manthorpe, 2012;Rowley et al, 2013;Sleeman and Saunders, 2013;McVey, 2013) and social care (Dunn et al, 2010;Boyle, 2011;Willner et al, 2012) settings. In particular, research has suggested shortcomings in assessing capacity by health and social care staff (Willner et al, 2011;Waight and Oldreive, 2011;Skinner et al, 2011;Roy et al, 2011;Lepping, 2011;Williams et al, 2012) and poor documentation of assessments of capacity and the decision-making process (Sorinmade et al, 2011). Although more recent research has highlighted some evidence of changing practice within health and social care (Manthorpe et al, 2014), the House of Lords Select Committee undertaking post-legislative scrutiny of the MCA concluded that:…”
Section: Introductionmentioning
confidence: 99%